Discontinuation versus continuation of renin–angiotensin system inhibitors in chronic kidney disease stage 3–5 patients: a systematic review and meta-analysis - Chen, I-Wen; Lin, Yi-Hsuan; Wu, Vin-Cent; Chen, Jui-Yi; Wu, Ming-Hsien (Frontiers in Pharmacology, 2025)
BackgroundRenin-angiotensin system inhibitors (RASi), comprising angiotensin-converting enzyme inhibitors (ACEi) or angiotensin II receptor blockers (ARB) are known for cardio- and renoprotection. However, there is uncertainty regarding the continuation of ACEi or ARB treatment in patients with chronic kidney disease (CKD) stages 3–5.MethodsIn this meta-analysis, we systematically searched all relevant studies published in PubMed, Embase, and the Cochrane Library up to 30 May 2024. Our objective was to assess the impacts of continuation or discontinuation of RASi in patients with CKD stages 3–5 on all-cause mortality, end-stage kidney disease, major adverse cardiovascular events (MACE), and hyperkalemia. We rated the certainty of the evidence using the Cochrane methods and the GRADE approach.ResultsThe search identified 520 studies, of which 8 studies, encompassing a total of 243,775 patients, were included in the analysis. The incidence of all-cause mortality was 40.3% (29,993 out of 74,447 patients), while ESKD occurred in 27.9% (8,992 out of 32,191 patients), MACE in 37.3% (11,225 out of 30,059 patients), and hyperkalemia in 39.4% (8,533 out of 21,642 patients). Pooled analysis revealed that patients who discontinued RASi therapy had a higher risk of developing ESKD compared to those who continued treatment [Hazard ratio (HR): 1.40, 95% confidence interval (CI): 1.19–1.65, P < 0.001], but a lower risk of hyperkalemia [Odds ratio (OR): 0.68, 95% CI: 0.60–0.77, P < 0.001]. There were no significant differences between the groups in all-cause mortality (HR: 1.34, 95% CI: 0.91–1.95, P = 0.135) and MACE (OR: 1.27, 95% CI: 0.93–1.73, P = 0.138).ConclusionPatients who discontinued RASi therapy exhibited a higher risk of developing ESKD but a reduced risk of hyperkalemia compared to those who continued RASi treatment. However, there were no significant differences in all-cause mortality and MACE between the two groups.Systematic Review Registrationidentifer, PROSPERO (CRD42023494698).